2017
DOI: 10.1186/s12891-017-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Pure exercise intolerance and ophthalmoplegia associated with the m.12,294G > A mutation in the MT-TL2 gene: a case report

Abstract: BackgroundPure exercise intolerance associated with exclusive affection of skeletal muscle is a very rare phenotype of patients with mitochondrial myopathy. Moreover, the exercise intolerance in these rare patients is yet not well explored, as most of known cases have not been assessed by objective testing, but only by interview. We report a patient with a mitochondrial DNA (mtDNA) mutation that gives rise to an exclusive myopathy associated with exercise intolerance and ophthalmoplegia. We quantified the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, the heteroplasmic G12294A variant disrupted a Watson-Crick base-pairing that was highly conserved in the anticodon stem of the tRNA Leu(CUN) [53], and biochemical analysis revealed that the G12294A significantly reduced activities of complexes I, III, and IV. Exercise physiological studies in the patient with this variant demonstrated a significantly reduced maximal oxygen uptake as well as threefold elevated lactate/pyruvate ratios strongly indicated that G12294A was pathogenic [54]. Furthermore, the G-to-A substitution at position 15995 occurred at anticodon stem of tRNA Pro , which was predicted to abolish the highly conserved Watson-Crick base-pairing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the heteroplasmic G12294A variant disrupted a Watson-Crick base-pairing that was highly conserved in the anticodon stem of the tRNA Leu(CUN) [53], and biochemical analysis revealed that the G12294A significantly reduced activities of complexes I, III, and IV. Exercise physiological studies in the patient with this variant demonstrated a significantly reduced maximal oxygen uptake as well as threefold elevated lactate/pyruvate ratios strongly indicated that G12294A was pathogenic [54]. Furthermore, the G-to-A substitution at position 15995 occurred at anticodon stem of tRNA Pro , which was predicted to abolish the highly conserved Watson-Crick base-pairing.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is an elusive symptom, which sometimes could be missed. However, exercise intolerance can be quantified through measurement of the maximal oxygen uptake, by evaluating resting and peak exerciseinduced serum lactate levels, as well as by examining lactate/pyruvate ratios [11]. Owing to exercise performance limitations, patients with exercise intolerance can be mistaken for having cardiopulmonary diseases.…”
Section: Exercise Intolerancementioning
confidence: 99%
“…Mt-tRNA defects manifested also with a CPEO phenotype, and several point mutations have been reported. A sporadic case of a heteroplasmic substitution in position 12316G>A in MT-TL2 causing cPEO with COX-negative fibers and RRF was described [99]; Karadimas CL et al described an m.12315G>A mutation in the MT-TL2 gene in a woman with cPEO [100]; Soldath P et al reported an m.12294 G>A in the MT-TL2 gene in an individual with cPEO and exercise intolerance [101].…”
Section: Defect Of Translational Apparatusmentioning
confidence: 99%